Production process of plant composite bacteriostatic care wet wipes
Patent Information
- Application Number
- CN202611271220.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]针对现有技术的不足,本发明提供了一种植物复合抑菌护理湿巾的生产工艺,解决了难溶性植物抑菌成分在复配成弱酸性浸透液时容易发生聚集析出、分散状态不稳定,以及传统增溶工艺易引发皮肤刺激的问题
1.本发明通过在加入酸液前对料液进行降温处理,并联动控制L-乳酸的滴加速度,减缓了黄芩苷在酸性环境下的质子化和聚集进程。低温配合缓慢的pH值下调,使新生成的难溶分子能够及时被体系中的海藻糖和无水甜菜碱网络包覆,减少了降酸过程引发的结晶析出现象,提高了浸透液在长期仓储中的分散稳定性。
Smart Images

Figure CN122954675A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of daily chemical product manufacturing technology, specifically to a production process for plant-based composite antibacterial care wipes. Background Technology
[0002] Nursing wipes typically use flexible materials such as spunlace nonwoven fabric as the base material, loaded with a penetrating liquid containing cleaning, moisturizing, and functional ingredients, and are widely used for skin cleansing and daily hygiene protection. In addition to basic stain removal, current nursing wipe products place high demands on gentleness when in contact with the skin. In recent years, compound antibacterial ingredients based on natural plant extracts have gradually become an important direction in the development of nursing wipe penetrating liquid formulations due to their lower irritation. Plant-derived active substances such as baicalin and eugenol have shown corresponding efficacy in inhibiting common microorganisms and are often compounded and used in these nursing products.
[0003] However, most plant extract antibacterial ingredients have low solubility in aqueous systems, posing challenges to actual compounding processes. For example, baicalin is difficult to dissolve directly in water, typically requiring the system to be adjusted to alkalinity to promote acid-base neutralization and salt formation. However, considering that human skin prefers a slightly acidic environment, the wet wipe soaking solution must be acidified in the final product stage to lower the pH. In traditional acid-lowering processes, rapid local acidity changes can easily cause baicalin to re-protonate, leading to rapid nucleation and crystallization, resulting in visible flocculation and unstable physical dispersion of the product. Existing conventional methods often involve adding large amounts of surfactants or organic solvents to the formula for forced solubilization. While this can maintain solution clarity to some extent, it easily disrupts the acid-base balance of the system and may increase the potential skin irritation of the final product, failing to fully meet the gentleness requirements of nursing wipes.
[0004] Furthermore, in processes involving multiple plant-based antibacterial components, essential oils such as eugenol are volatile, and their physical state is easily affected by fluctuations in ambient temperature. Conventional heating and compounding processes often lead to the volatilization and loss of these components under high-temperature stirring, affecting the actual retention rate of the effective components in the finished product. Simultaneously, when oily components are directly mixed into an aqueous system, differences in interfacial tension and sudden changes in temperature and acidity can easily cause droplet aggregation and demulsification, making it difficult to maintain a long-term homogeneous distribution of the composite impregnation solution.
[0005] Therefore, the present invention provides a production process for plant-based composite antibacterial nursing wipes to address the shortcomings of existing technologies. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a production process for plant-based composite antibacterial nursing wipes, which solves the problems of poorly soluble plant antibacterial ingredients easily agglomerating and precipitating, having unstable dispersion, and skin irritation caused by traditional solubilization processes when compounded into a weakly acidic impregnation solution.
[0007] To achieve the above objectives, the present invention provides a production process for plant-based composite antibacterial care wipes, employing the following technical solution: A production process for plant-based composite antibacterial nursing wipes includes the following steps: S1. Add deionized water to the main reactor equipped with a jacketed temperature control system and a mechanical stirrer, turn on the heating, and maintain the water temperature at the first set temperature. S2, add anhydrous betaine and trehalose in sequence and stir until dissolved; add L-arginine to make the system alkaline pH value, then add baicalin and continue stirring to form a homogeneous solution; S3, turn off heating, start cooling circulation, cool the liquid to a second set temperature of 10 to 15°C at a set cooling rate, and maintain this temperature; S4, while maintaining the second set temperature and continuous stirring, the eugenol solubilized premixed solution formed by premixing dipropylene glycol, eugenol and tea saponin is pumped into the main reactor at a uniform rate and mixed evenly. S5, under the condition of maintaining the second set temperature and continuous stirring, add L-lactic acid aqueous solution dropwise into the main reaction vessel, adjust the dropwise flow rate of L-lactic acid aqueous solution to keep the pH value decreasing rate within the specified range of 0.05 to 0.15 pH value units per minute, and stop the dropwise addition when the pH of the system reaches 5.0 to 5.5. This stop dropwise addition point is the low temperature acidification endpoint; S6, stop cooling and allow the temperature of the liquid to rise to 20 to 25°C, stir to balance; add deionized water and fine-tune the pH to bring the final pH of the system to 5.0 to 5.5, and stir evenly; S7, the liquid is conveyed through the microporous filter membrane, the filtrate is collected, and the plant composite antibacterial impregnation liquid is obtained; S8. The obtained impregnation liquid is applied to the spunlace nonwoven fabric substrate, folded and cut, and then sealed in packaging material to obtain plant composite antibacterial care wipes.
[0008] By adopting the above technical solution, this application proposes a dispersion process that relies on a combination of physical temperature control and chemical acid-base adjustment. Baicalin, due to the presence of phenolic hydroxyl groups in its structure, is difficult to dissolve in water at room temperature. After adding L-arginine in step S2, the system becomes alkaline. L-arginine neutralizes the acid-base reaction with baicalin, forming a water-soluble salt and promoting its dissolution in the aqueous phase. Based on this, the polar groups in the molecular structures of anhydrous betaine and trehalose cross-link in solution to form a hydrogen bond network structure.
[0009] Furthermore, considering the final product's requirement for a weakly acidic environment, L-lactic acid needs to be added to adjust the pH of the system. Direct acid addition can easily cause sudden changes in local pH, prompting baicalin salts to reprotonate and rapidly aggregate, resulting in flocculation and precipitation. Therefore, the process in this application lowers the system temperature before adding L-lactic acid, utilizing the low temperature environment to slow down molecular thermal motion and collision frequency. Under this temperature condition, the dropping rate of L-lactic acid is controlled by a linkage device, making the protonation process of baicalin relatively gentle. Because the formation rate is controllable, the newly formed baicalin molecules have time to interact with the pre-formed trehalose and anhydrous betaine network within the system before macroscopic aggregation. With the help of the steric hindrance provided by these components, most baicalin molecules can be dispersed and suspended in the aqueous phase at a relatively small size, thereby improving the crystallization problem caused by the acid reduction operation.
[0010] During this process, the eugenol solubilized premix is added under the aforementioned cooling and slow acidification conditions, avoiding the consumption of volatile essential oil components by initial heating or localized exothermic reactions. Simultaneously, the hydrogen bond network within the system also provides a certain degree of coating for the eugenol droplets, which helps maintain the physical dispersion of the entire composite system and lays the foundation for maintaining the performance of the product under actual storage conditions.
[0011] Preferably, the raw materials used in the production process comprise the following components in parts by weight: The initial amount of deionized water added is 880.0 to 920.0 parts by weight, determined based on the amounts of other components and pH adjustment solution, so that the final amount of deionized water can be replenished to 1000.0 parts by weight. Anhydrous betaine: 2.0 to 8.0 parts; Trehalose: 5.0 to 15.0 parts; L-Arginine: 0.5 to 3.0 parts; Baicalin: 1.0 to 5.0 parts; L-lactic acid aqueous solution: the amount required to bring the system to the specified pH; Added deionized water: the amount required to bring the total weight of the system to 1000.0 parts by weight; In the eugenol solubilized premix, the weight parts of dipropylene glycol, eugenol and tea saponin are respectively: 10.0 to 30.0 parts of dipropylene glycol, 0.1 to 1.0 parts of eugenol and 1.0 to 5.0 parts of tea saponin.
[0012] By adopting the above technical solution, the appropriate dosage range of each functional component is defined. Baicalin and eugenol, at this ratio, can provide corresponding microbial inhibitory effects. Dipropylene glycol and tea saponin work synergistically to help reduce the interfacial tension of the system and promote the dissolution of eugenol. The matching dosage of trehalose and anhydrous betaine can provide suitable steric hindrance protection for the dispersion while controlling the system viscosity to avoid excessively high levels.
[0013] Preferably, the preparation method of the eugenol solubilized premix is as follows: in an auxiliary reaction vessel, the temperature of the material in the auxiliary reaction vessel is controlled at 20 to 25°C, and the dipropylene glycol, eugenol and tea saponin are added in sequence; the stirrer is turned on and the speed is set to 200 to 400 rpm, and the mixture is mixed for 15 to 30 minutes to obtain a uniform and transparent eugenol solubilized premix.
[0014] By employing the above technical solution, a pre-mixed solubilized solution is prepared, reducing the impact of moisture on the initial dispersion process of eugenol. Tea saponin molecules contact eugenol in the dipropylene glycol medium, pre-forming aggregate structures, which helps reduce the risk of stratification caused by abrupt changes in interfacial composition when subsequently introduced into the main aqueous phase.
[0015] Preferably, in step S1, the first set temperature is 40 to 45°C; in step S2, after adding L-arginine, the stirring speed is maintained at 100 to 150 rpm, and after adding baicalin, the stirring is continued for 15 to 30 minutes.
[0016] By adopting the above technical solution, an environment of 40 to 45°C can assist in the dissolution of anhydrous betaine and trehalose. Controlling the pH value within the weakly alkaline range of 8.5 to 9.0 not only helps the dissociation and dissolution of phenolic hydroxyl groups in baicalin, but also avoids degradation or side reactions of plant active ingredients caused by excessive alkalinity.
[0017] Preferably, in step S3, the cooling rate is 1 to 3 °C / min.
[0018] By adopting the above technical solution and controlling the cooling rate to 1 to 3 °C / min, thermal shock can be mitigated, reducing the possibility of spontaneous nucleation of the solute. An environment of 10 to 15 °C restricts molecular thermal motion while preserving the basic fluidity of the liquid, which is beneficial for mixing and diffusion when acid is subsequently added.
[0019] Preferably, in step S4, the eugenol solubilized premix is pumped into the main reactor at a constant rate over 5 to 15 minutes.
[0020] By adopting the above technical solution, the feeding rate is limited, allowing the premixed liquid to obtain a certain interphase diffusion time under stirring conditions, thereby reducing the phenomenon of excessively high local concentration caused by instantaneous injection.
[0021] Preferably, in step S5, the L-lactic acid aqueous solution is an L-lactic acid aqueous solution with a mass fraction of 10.0% based on L-lactic acid.
[0022] By employing the above-mentioned technical solution, the rate of pH decrease is controlled at 0.05 to 0.15 pH units per minute, thus slowing down the conversion of baicalin from salt to molecular form. This slower conversion pace facilitates the encapsulation of newly generated free baicalin molecules by the surrounding trehalose and anhydrous betaine network, thereby reducing the risk of precipitation during the acid reduction process. Simultaneously, the system is adjusted to a pH range of 5.0 to 5.5, which is relatively close to the pH of human skin.
[0023] Preferably, in step S6, the temperature of the recovered liquid is 20 to 25°C, and the stirring equilibrium time is 20 to 40 minutes. During fine-tuning, an L-lactic acid aqueous solution with a mass fraction of 10.0% based on L-lactic acid or an L-arginine aqueous solution with a mass fraction of 10.0% based on L-arginine is used for adjustment. Finally, deionized water is added to make the total weight of the system reach 1000.0 parts by weight.
[0024] By adopting the above technical solution, after the acid addition is completed, the system is restored to room temperature and stirred to achieve equilibrium. This can alleviate the internal stress caused by the cooling and acid reduction operations, promote the stable interaction between components, and help maintain the physical stability during subsequent filling and storage.
[0025] Preferably, in step S7, the pore size of the microporous filter membrane is 0.5 to 2.0 μm; after the feed liquid is transported through the microporous filter membrane, the filtrate is collected, which is the plant composite antibacterial impregnation solution.
[0026] By adopting the above technical solution, the pore size can block mechanical impurities and some large particle aggregates that may be mixed in, while allowing highly dispersed active ingredients to pass through, which helps to improve the appearance uniformity of the impregnation liquid.
[0027] Preferably, in step S8, the impregnation liquid is applied to the spunlace nonwoven fabric substrate at a mass ratio of 1:2.5-4.5 between the unimpregnated spunlace nonwoven fabric substrate and the impregnation liquid. The substrate is then folded, cut, and sealed in packaging material to obtain the finished product.
[0028] By adopting the above technical solution, the fiber pores of the spunlace nonwoven fabric within this ratio range have a good load-bearing effect on the impregnation liquid, avoiding the dryness caused by insufficient liquid volume and reducing the leakage caused by excessive liquid volume, making the product more suitable in actual use.
[0029] This invention provides a production process for plant-based composite antibacterial nursing wipes. It has the following beneficial effects: 1. This invention slows down the protonation and aggregation process of baicalin in an acidic environment by cooling the feed solution before adding acid and controlling the dropping rate of L-lactic acid. The low temperature combined with slow pH adjustment allows newly formed insoluble molecules to be promptly coated by the trehalose and anhydrous betaine network in the system, reducing crystallization caused by the acid reduction process and improving the dispersion stability of the impregnation solution during long-term storage.
[0030] 2. This invention utilizes L-arginine to initially adjust the system to a weakly alkaline state, promoting the acid-base neutralization and dissolution of plant antibacterial components containing phenolic hydroxyl groups, forming salts. Subsequently, anhydrous betaine and trehalose provide steric hindrance. This dispersion process, relying on a combination of gentle acid-base adjustment and hydrogen bond networks, replaces the large amounts of strong surfactants or organic solvents used in conventional formulations, ensuring the dissolution of active ingredients while reducing the potential skin irritation of the final product.
[0031] 3. In this invention, the eugenol solubilized premix is pumped into the main reactor during the cooling and slow acid reduction stage, avoiding the initial heating process. This operation reduces the volatilization loss of volatile essential oil components such as eugenol due to heating, and also avoids the problem of demulsification caused by excessively high temperature or sudden changes in acidity, ensuring the uniform distribution and efficacy of the compound antibacterial components in the aqueous system. Attached Figure Description
[0032] Figure 1 This is a comparison chart of the retention rate of transmittance during centrifugation of various embodiments and comparative samples of the present invention; Figure 2 This is a graph showing the cumulative release trend of baicalin under different release conditions in Examples 1 and 2 of the present invention; Figure 3 This is a graph showing the relationship between the retention rate of active ingredients and color difference values for various embodiments and comparative samples of the present invention; Figure 4 This is a graph showing the relationship between the headspace area of eugenol and the average retention rate of antibacterial activity after drying for samples with the same initial eugenol content according to the present invention. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] The main raw materials and reagents used in the following examples and comparative examples are as follows. Unless otherwise specified, all reagents are commercially available analytical grade or higher grade products.
[0035] Baicalin, CAS number 21967-41-9, molecular formula C 21 H 18 O 11 Purity mass fraction ≥85%.
[0036] Eugenol, CAS No. 97-53-0, purity mass fraction ≥99%.
[0037] Tea saponin, CAS number 8047-15-2, is a mixture of triterpenoid saponin compounds with a purity of ≥60% by mass. The surface tension of a 0.5% aqueous solution at 25℃ is 32-40 mN / m.
[0038] Anhydrous betaine, CAS No. 107-43-7, purity ≥98% by mass.
[0039] Trehalose, CAS number 99-20-7, purity mass fraction ≥99%.
[0040] L-arginine, CAS number 74-79-3, purity mass fraction ≥99%.
[0041] L-lactic acid, CAS number 79-33-4, purity mass fraction ≥85%, should be converted according to the actual purity of the raw material and prepared into an aqueous solution with a mass fraction of 10.0% based on L-lactic acid using deionized water.
[0042] Dipropylene glycol, CAS number 25265-71-8, purity mass fraction ≥99%.
[0043] Deionized water with a conductivity ≤2.0μS / cm.
[0044] Spunlace nonwoven fabric with a surface density of 40–60 g / m² 2 .
[0045] Preparation Example 1: This preparation example provides a method for preparing eugenol solubilized premix, including the following steps: (1) In an auxiliary reaction vessel at 25°C, add 20.0 parts of dipropylene glycol, 0.5 parts of eugenol and 3.0 parts of tea saponin in sequence; (2) Turn on the stirrer, set the speed to 300 rpm, mix for 20 minutes to obtain a uniform and transparent eugenol solubilized premix, hereinafter referred to as the premix.
[0046] Preparation Example 2: This preparation example provides a method for preparing eugenol solubilized premix, including the following steps: (1) In an auxiliary reaction vessel at 20°C, add 10.0 parts of dipropylene glycol, 0.1 parts of eugenol and 1.0 parts of tea saponin in sequence; (2) Turn on the stirrer, set the speed to 200 rpm, mix for 15 minutes to obtain a uniform and transparent eugenol solubilized premix.
[0047] Preparation Example 3: This preparation example provides a method for preparing eugenol solubilized premix, including the following steps: (1) In an auxiliary reaction vessel at 25°C, add 30.0 parts of dipropylene glycol, 1.0 part of eugenol and 5.0 parts of tea saponin in sequence; (2) Turn on the stirrer, set the speed to 400 rpm, mix for 30 minutes to obtain a uniform and transparent eugenol solubilized premix.
[0048] Example 1:
[0049] This embodiment provides a production process for plant-based composite antibacterial nursing wipes, including the following steps: (1) Add 920.0 parts of deionized water to the main reactor equipped with a jacketed temperature control system and a mechanical stirrer, turn on the jacket heating, and maintain the water temperature at 45°C; (2) Add 5.0 parts of anhydrous betaine and 10.0 parts of trehalose in sequence and stir until completely dissolved; add 1.8 parts of L-arginine. At this time, the online pH meter shows that the pH of the system is 8.8. Maintain the stirring speed at 120 rpm, add 3.0 parts of baicalin, and continue stirring for 20 minutes to form a homogeneous solution. (3) Turn off the heating and turn on the jacket cooling circulation to cool the liquid to 12°C at a cooling rate of 2°C / min and maintain this temperature; (4) Increase the stirring speed to 200 rpm, and use a metering pump to uniformly pump the eugenol solubilized premix obtained in Preparation Example 1 into the main reactor within 10 minutes to mix evenly; (5) Start the metering pump and add L-lactic acid aqueous solution with a mass fraction of 10.0% by L-lactic acid dropwise into the main reactor. Adjust the dropwise flow rate of L-lactic acid aqueous solution to keep the pH value of the solution decreasing within the specified range of 0.10 pH units / minute. When about 12.0 parts of L-lactic acid aqueous solution are consumed and the pH value of the system reaches 5.2, stop the dropwise addition. (6) Stop cooling, introduce room temperature water to raise the temperature of the liquid to 25°C, adjust the speed to 80 rpm, and stir for 30 minutes to balance; add deionized water to bring the total weight of the system to approximately 1000.0 parts, and reserve the amount of pH fine-tuning solution to be added. Stir evenly and retest the pH value of the system; if necessary, use a 10.0% L-lactic acid aqueous solution or a 10.0% L-arginine aqueous solution to fine-tune the pH value; finally, add deionized water to bring the total weight of the system to 1000.0 parts, stir evenly, and confirm again that the final pH value of the system is 5.2±0.1. (7) The liquid is transported through a microporous filter membrane with a pore size of 1.0 μm and the filtrate is collected. This is the plant composite antibacterial impregnation liquid, hereinafter referred to as the impregnation liquid. (8) The impregnation liquid is applied to the spunlace nonwoven fabric substrate at a mass ratio of 1:3.5. After folding and cutting, the substrate is sealed in packaging material to obtain the finished product.
[0050] Example 2:
[0051] This embodiment provides a production process for plant-based composite antibacterial nursing wipes, including the following steps: (1) Add 900.0 parts of deionized water to the main reactor equipped with a jacketed temperature control system and a mechanical stirrer, turn on the jacket heating, and maintain the water temperature at 40°C; (2) Add 2.0 parts of anhydrous betaine and 5.0 parts of trehalose in sequence and stir until completely dissolved; add 0.5 parts of L-arginine. At this time, the online pH meter shows that the pH of the system is 8.5. Maintain the stirring speed at 100 rpm, add 1.0 parts of baicalin, and continue stirring for 15 minutes to form a uniform solution. (3) Turn off the heating and turn on the jacket cooling circulation to cool the liquid to 10°C at a cooling rate of 1°C / min and maintain the temperature. (4) Increase the stirring speed to 150 rpm and pump the eugenol solubilized premix obtained in Preparation Example 2 into the main reactor at a constant speed within 5 minutes using a metering pump, and mix evenly. (5) Start the metering pump and add L-lactic acid aqueous solution with a mass fraction of 10.0% by L-lactic acid dropwise into the main reactor. Adjust the dropwise flow rate of L-lactic acid aqueous solution to keep the pH value of the solution decreasing within the specified range of 0.05 pH units / minute. When about 5.0 parts of L-lactic acid aqueous solution are consumed and the pH value of the system reaches 5.5, stop the dropwise addition. (6) Stop cooling, introduce room temperature water to raise the temperature of the liquid to 20°C, adjust the speed to 50 rpm, and stir for 20 minutes to balance; add deionized water to bring the total weight of the system to approximately 1000.0 parts, and reserve the amount of pH fine-tuning solution to be added. Stir evenly and retest the pH value of the system; if necessary, use an L-lactic acid aqueous solution with a mass fraction of 10.0% or an L-arginine aqueous solution with a mass fraction of 10.0% for fine-tuning; finally, add deionized water to bring the total weight of the system to 1000.0 parts, stir evenly, and confirm again that the final pH value of the system is 5.5±0.1. (7) The liquid is transported through a microporous filter membrane with a pore size of 0.5 μm, and the filtrate is collected, which is the plant composite antibacterial impregnation liquid; (8) The impregnation liquid is applied to the spunlace nonwoven fabric substrate at a mass ratio of 1:2.5, and after folding and cutting, it is packed into packaging material and sealed to obtain the finished product.
[0052] Example 3:
[0053] This embodiment provides a production process for plant-based composite antibacterial nursing wipes, including the following steps: (1) Add 880.0 parts of deionized water to the main reactor equipped with a jacketed temperature control system and a mechanical stirrer, turn on the jacket heating, and maintain the water temperature at 45°C; (2) Add 8.0 parts of anhydrous betaine and 15.0 parts of trehalose in sequence and stir until completely dissolved; add 3.0 parts of L-arginine. At this time, the online pH meter shows that the pH of the system is 9.0. Maintain the stirring speed at 150 rpm, add 5.0 parts of baicalin, and continue stirring for 30 minutes to form a homogeneous solution. (3) Turn off the heating and turn on the jacket cooling circulation to cool the liquid to 15°C at a cooling rate of 3°C / min and maintain this temperature; (4) Increase the stirring speed to 250 rpm, and use a metering pump to uniformly pump the eugenol solubilized premix obtained in Preparation Example 3 into the main reactor within 15 minutes to mix evenly; (5) Start the metering pump and add L-lactic acid aqueous solution with a mass fraction of 10.0% by L-lactic acid dropwise into the main reactor. Adjust the dropwise flow rate of L-lactic acid aqueous solution to keep the pH value of the feed solution decreasing within the specified range of 0.15 pH units / minute. When about 20.0 parts of L-lactic acid aqueous solution are consumed and the pH value of the system reaches 5.0, stop the dropwise addition. (6) Stop cooling, introduce room temperature water to raise the temperature of the liquid to 25°C, adjust the speed to 100 rpm, and stir for 40 minutes to balance; add deionized water to bring the total weight of the system to approximately 1000.0 parts, and reserve the amount of pH fine-tuning solution to be added. Stir evenly and retest the pH value of the system; if necessary, use a 10.0% L-lactic acid aqueous solution or a 10.0% L-arginine aqueous solution to fine-tune the pH value; finally, add deionized water to bring the total weight of the system to 1000.0 parts, stir evenly, and confirm the final pH value of the system to 5.0±0.1. (7) The liquid is transported through a microporous filter membrane with a pore size of 2.0 μm, and the filtrate is collected, which is the plant composite antibacterial impregnation liquid; (8) The impregnation liquid is applied to the spunlace nonwoven fabric substrate at a mass ratio of 1:4.5, and after folding and cutting, it is packed into packaging material and sealed to obtain the finished product.
[0054] Example 4:
[0055] This embodiment provides a production process for plant-based composite antibacterial nursing wipes, including the following steps: (1) Add 920.0 parts of deionized water to the main reactor equipped with a jacketed temperature control system and a mechanical stirrer, turn on the jacket heating, and maintain the water temperature at 45°C; (2) Add 3.0 parts of anhydrous betaine and 12.0 parts of trehalose in sequence and stir until completely dissolved; add 1.8 parts of L-arginine. At this time, the online pH meter shows that the pH of the system is 8.8. Maintain the stirring speed at 120 rpm, add 3.0 parts of baicalin, and continue stirring for 20 minutes to form a homogeneous solution. (3) Turn off the heating and turn on the jacket cooling circulation to cool the liquid to 12°C at a cooling rate of 2°C / min and maintain this temperature; (4) Increase the stirring speed to 200 rpm, and use a metering pump to uniformly pump the eugenol solubilized premix obtained in Preparation Example 1 into the main reactor within 10 minutes to mix evenly; (5) Start the metering pump and add L-lactic acid aqueous solution with a mass fraction of 10.0% by L-lactic acid dropwise into the main reactor. Link the online pH meter to control the flow rate so that the pH value of the feed solution decreases at a rate of 0.10 pH units / minute. When about 12.0 parts of L-lactic acid aqueous solution are consumed and the pH value of the system reaches 5.2, stop the dropwise addition. (6) Stop cooling, introduce room temperature water to raise the temperature of the liquid to 25°C, adjust the speed to 80 rpm, and stir for 30 minutes to balance; add deionized water to bring the total weight of the system to approximately 1000.0 parts, and reserve the amount of pH fine-tuning solution to be added. Stir evenly and retest the pH value of the system; if necessary, use a 10.0% L-lactic acid aqueous solution or a 10.0% L-arginine aqueous solution to fine-tune the pH value; finally, add deionized water to bring the total weight of the system to 1000.0 parts, stir evenly, and confirm again that the final pH value of the system is 5.2±0.1. (7) The liquid is transported through a microporous filter membrane with a pore size of 1.0 μm, and the filtrate is collected, which is the plant composite antibacterial impregnation liquid; (8) The impregnation liquid is applied to the spunlace nonwoven fabric substrate at a mass ratio of 1:3.5. After folding and cutting, the substrate is sealed in packaging material to obtain the finished product.
[0056] Comparative Example 1: Compared with Example 1, the difference is that: in step (3), no cooling operation is performed, the liquid is kept at 45°C, and the subsequent addition of eugenol solubilization premix and L-lactic acid drop addition are completed at 45°C; after the L-lactic acid drop addition is completed, the jacket cooling cycle is turned on to reduce the temperature of the liquid to 25°C, and then the remaining operations of step (6) of Example 1 are performed, and the rest are the same.
[0057] Comparative Example 2: Compared with Example 1, the difference is that in step (5), the dripping flow rate of L-lactic acid aqueous solution is not controlled, that is, the rate of pH decrease is not controlled. 12.0 parts of L-lactic acid aqueous solution with a mass fraction of 10.0% based on L-lactic acid are rapidly and continuously added to the main reactor within 1 minute. The rest are the same.
[0058] Comparative Example 3: Compared with Example 1, the difference is that trehalose is not added to the raw material formula in step (2), and the amount of deionized water added in step (1) is adjusted from 920.0 parts to 930.0 parts, while the rest are the same.
[0059] Comparative Example 4: Compared with Example 1, the difference is that anhydrous betaine is not added to the raw material formula in step (2), and the amount of deionized water added in step (1) is adjusted from 920.0 parts to 925.0 parts, while the rest are the same.
[0060] Comparative Example 5: Compared with Example 1, the difference is that: no tea saponin was added to the eugenol solubilization premix of Example 1, and the premix consisted of only 20.0 parts of dipropylene glycol and 0.5 parts of eugenol; the amount of deionized water added in step (1) of Example 1 was adjusted from 920.0 parts to 923.0 parts, and the rest were the same.
[0061] Test Example 1: Experimental Description: This test is used to compare the effects of different process parameters and formulation composition on the dispersion stability of wet wipe soaking liquid. The centrifugal dispersion stability of each sample under the set centrifugation conditions is evaluated by measuring the initial turbidity and transmittance of each sample before and after centrifugation.
[0062] Experimental steps: (1) Take 20 mL of the impregnation samples prepared in Examples 1 to 4 and Comparative Examples 1 to 5 and place them in clean glass colorimetric tubes. At an ambient temperature of 25°C, use a turbidity meter to measure the initial turbidity of each sample in sequence and record the NTU test value.
[0063] (2) Transfer each of the above samples into a 50mL standard centrifuge tube, place it in a benchtop high-speed centrifuge, set the speed to 4000 rpm, the corresponding relative centrifugal force to 2147×g, and centrifuge continuously for 30 minutes.
[0064] (3) After centrifugation, let stand for 10 minutes. Without disturbing the sediment or flocculation layer at the bottom of the tube, carefully draw the liquid from a position about one-third of the total height of the liquid column from the bottom of the tube.
[0065] (4) Using a UV-Vis spectrophotometer, at a wavelength of 600 nm, with deionized water as a blank control, the transmittance of the original sample before centrifugation and the transmittance of the lower liquid phase after centrifugation were measured respectively.
[0066] (5) Three independent parallel samples were set up for each group of experiments. The data in Table 1 are the average values of the three independent parallel samples.
[0067] Table 1: Turbidity and Centrifugal Transmittance Test Results of Each Example and Comparative Sample
[0068] Results and Analysis: According to Table 1 and Figure 1 The test results showed that, under the test conditions, the initial turbidity of Examples 1 to 4 was 1.92–2.87 NTU, the transmittance before centrifugation was 97.4%–99.1%, and the transmittance of the lower liquid phase after centrifugation was 96.5%–98.7%. The relatively low initial turbidity of Examples 1 to 4 and the small change in transmittance before and after centrifugation indicate that the corresponding impregnation samples maintained a relatively uniform dispersion state under the set centrifugation conditions and had good centrifugal dispersion stability.
[0069] Compared to Example 1, Comparative Example 5, which did not contain tea saponin, showed an increased initial turbidity of 108.34 NTU and a decreased transmittance of the lower liquid phase to 8.5% after centrifugation. These results suggest that the absence of tea saponin may weaken the solubilizing and dispersing effects of the system and increase the tendency for poorly soluble components to aggregate, thereby adversely affecting the centrifugal dispersion stability of the impregnation solution.
[0070] Comparative Example 1 did not involve cooling, and the addition of the eugenol solubilizing premix and the dropwise addition of the L-lactic acid aqueous solution were completed at 45°C. Comparative Example 2 did not control the dropwise flow rate of the L-lactic acid aqueous solution. Compared to Example 1, the initial turbidity of both Comparative Example 1 and Comparative Example 2 was increased, and the transmittance of the lower liquid phase after centrifugation was decreased. These results suggest that adjusting the pH at higher temperatures or adding the L-lactic acid aqueous solution too quickly may affect the dispersion of poorly soluble components and increase the likelihood of aggregation or precipitation. Combining cooling with controlled pH decrease rate may help maintain the dispersion of the impregnation solution system.
[0071] Comparative Examples 3 and 4, without the addition of trehalose and anhydrous betaine, respectively, showed lower liquid phase transmittances of 86.4% and 88.9% after centrifugation, both lower than the 97.8% of Example 1. These results suggest that the absence of trehalose and anhydrous betaine may affect the aqueous environment and inter-component interactions, thereby reducing the centrifugal dispersion stability of the impregnation solution. Therefore, under the test conditions, trehalose and anhydrous betaine may each play a certain auxiliary role in maintaining the dispersion stability of the impregnation solution system.
[0072] Based on the above results, under the set centrifugation test conditions, Examples 1 to 4 showed relatively good centrifugal dispersion stability. The process temperature, the rate of addition of L-lactic acid aqueous solution, and the formulation settings of tea saponin, trehalose, and anhydrous betaine may all affect the dispersion state of the impregnation liquid system.
[0073] Test Example 2: Experimental Description: This test was used to examine the release behavior of baicalin in wet wipe soaking liquid under different external environmental conditions. By comparing the cumulative release of baicalin under 25℃ deionized water conditions and 35℃ simplified simulated artificial sweat conditions, the differences in release characteristics of the system under different temperature and release medium combinations were evaluated.
[0074] Experimental steps: (1) Take an appropriate amount of regenerated cellulose dialysis bag with a molecular weight cutoff of 3500 Da, boil it in deionized water for 15 minutes, rinse it repeatedly with deionized water before use, and soak it at room temperature for later use.
[0075] (2) Preparation of simplified simulated artificial sweat: Add sodium chloride to deionized water to make its mass fraction 0.5%, and then add L-lactic acid aqueous solution with a mass fraction of 10.0% to adjust the pH value of the solution to 5.5.
[0076] (3) Set up 3 independent parallel samples according to each release condition. Accurately transfer 10 mL of the permeation solution prepared in Example 1 and Example 2 into each parallel sample and put it into a pretreated dialysis bag. After removing the internal air, seal both ends of the dialysis bag with a special clamp. Independent dialysis bags were used in Example 1 and Example 2 under the two release conditions respectively.
[0077] (4) Four release condition combinations were set up: the release system of the sample from Example 1 in deionized water at 25°C, the release system of the sample from Example 2 in deionized water at 25°C, the release system of the sample from Example 1 in simplified simulated artificial sweat at 35°C, and the release system of the sample from Example 2 in simplified simulated artificial sweat at 35°C. Each condition combination was set up with 3 independent parallel systems, and each dialysis bag was placed in a beaker containing 200 mL of the corresponding release medium.
[0078] (5) Turn on the magnetic stirring function of each group of constant temperature water baths and set the speed to 100 rpm. At each time point of 0.5 hours, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours and 24 hours, take 3 mL of release medium from each beaker and immediately add 3 mL of fresh corresponding medium at the same temperature to the beaker.
[0079] (6) The content of baicalin in the extracted release medium was determined by high performance liquid chromatography (HPLC). A C18 reversed-phase column with dimensions of 250 mm × 4.6 mm and a packing particle size of 5 μm was used. Gradient elution was performed using methanol (phase A) and a 0.1% (w / w) phosphoric acid aqueous solution (phase B) as the mobile phase. The gradient elution program was set as follows: 0–10 minutes, the volume fraction of phase A linearly increased from 40% to 55%; 10–20 minutes, the volume fraction of phase A linearly increased from 55% to 70%; 20–30 minutes, the volume fraction of phase A decreased from 70% back to 40% and equilibrated. The flow rate was set to 1.0 mL / min, the column temperature was maintained at 30℃, and the detection wavelength was 277 nm. Qualitative analysis was performed based on the retention time of the baicalin reference standard, and quantitative analysis was performed using an external standard curve. The chromatographic conditions used effectively separated the baicalin peak from the chromatographic peaks of eugenol and other formulation components.
[0080] (7) The cumulative release at each sampling time point is calculated by multiplying the baicalin concentration measured at the current time point by the total volume of the release medium, plus the sum of the products of the volume of each previous single sampling and the concentration at the corresponding time point. Then, based on the total amount of baicalin measured by high performance liquid chromatography in the corresponding 10 mL of dialysis solution before being placed into the dialysis bag, the cumulative release rate of baicalin at each time point is calculated.
[0081] (8) Three independent parallel samples were set up for each group of experiments. The data in Table 2 are the average values of the three independent parallel samples.
[0082] Table 2: Cumulative release rate of baicalin in different environmental media in the examples
[0083] Note: Data in the table is in percent.
[0084] Results and Analysis: From Table 2 and Figure 2 As can be seen, under deionized water conditions at 25°C, the cumulative release rates of baicalin in both Examples 1 and 2 gradually increased with time, reaching 45.18% and 46.72% respectively after 24 hours. Under the conditions of this experiment, both showed a relatively gradual release trend overall. This release behavior may be related to factors such as the dialysis membrane mass transfer process, the properties of the release medium, and the interactions between components in the permeate system. The existing experimental results are insufficient to attribute the above release characteristics to a single factor.
[0085] Under simplified simulated artificial sweat conditions at 35°C, the cumulative release rate of baicalin in Examples 1 and 2 was significantly higher than that under the corresponding deionized water conditions at 25°C; the cumulative release rates at 4 hours both exceeded 60%, and reached 91.53% and 93.81% respectively at 24 hours. These results suggest that, under the experimental setup, variations in the combination of temperature and the composition of the release medium may affect the release process of baicalin, thereby increasing its cumulative release level.
[0086] It should be noted that the temperature and release medium conditions in this experiment were combined and changed simultaneously; no separate single-factor controls were set up for temperature or medium composition. Therefore, the existing data mainly reflect the differences in baicalin release behavior under different environmental conditions, and the increased release rate cannot be attributed solely to increased temperature, the addition of sodium chloride, pH changes, or other single medium factors.
[0087] In summary, the results show that baicalin in the impregnation system of this invention exhibits different release behaviors under different external environmental conditions: its release process is relatively slow under deionized water conditions at 25°C; and its cumulative release rate increases rapidly under simplified simulated artificial sweat conditions at 35°C. These results can be used to characterize the differences in release behavior of the system under different temperature and release medium combinations, but they should not be used to directly infer that the dispersion state of the impregnation system has changed, nor should they be used directly as an evaluation basis for the actual packaging and storage stability of wet wipe products. Related performance still needs to be verified through targeted experiments.
[0088] Test Example 3: Experimental Description: This test is used to compare the effects of different process parameters and formulation composition on the chemical stability and appearance color changes of wet wipe soaking liquid under accelerated aging conditions. By measuring the content of baicalin and eugenol before and after accelerated aging, as well as the color difference value of the samples, the retention of active ingredients and appearance color stability of each sample under the set accelerated aging conditions are evaluated.
[0089] Experimental steps: (1) Extract the permeate samples prepared in Examples 1 to 4 and Comparative Examples 1 to 5, and put them into clean transparent glass vials and seal them. Place all samples in a constant temperature incubator at 54°C for 14 consecutive days for accelerated aging treatment.
[0090] (2) Unaged original samples were retained as initial controls. Using a benchtop colorimeter under standard light source D65 conditions, the L*, a*, and b* values of each sample before and after aging were measured, where L* represents the lightness of the sample, a* represents the red-green hue of the sample, and b* represents the yellow-blue hue of the sample. The total color difference ΔE of each group of samples before and after aging was calculated according to the CIELAB color difference formula.
[0091] (3) Accurately pipette 2.0 mL of each sample before and after aging, add methanol to make up to 10.0 mL, extract by ultrasonication for 15 minutes, filter with a 0.45 μm microporous membrane, and collect the filtrate as the test solution.
[0092] (4) The test solution was analyzed using high performance liquid chromatography (HPLC). A C18 reversed-phase column with dimensions of 250 mm x 4.6 mm and a packing particle size of 5 μm was used. Gradient elution conditions were employed, validated by the methodology and capable of effectively separating baicalin, eugenol, and adjacent impurity peaks. The mobile phase consisted of methanol as phase A and 0.1% (w / w) aqueous phosphoric acid solution as phase B. The gradient elution program was set as follows: from 0 to 15 minutes, the volume fraction of phase A linearly increased from 45% to 65%; from 15 to 25 minutes, the volume fraction of phase A linearly increased from 65% to 80%; and from 25 to 35 minutes, the volume fraction of phase A decreased from 80% back to 45% and equilibrated. The column temperature was maintained at 30 °C, the detection wavelength was set at 277 nm, and the flow rate was 1.0 mL / min.
[0093] (5) Record the chromatographic peak areas of baicalin and eugenol before and after aging, calculate the content of each sample before and after aging using the external standard method, and calculate the retention rates of baicalin and eugenol after accelerated aging of the two main active ingredients.
[0094] (6) Three independent parallel samples were set up for each group of experiments. The data in Table 3 are the average values of the three independent parallel samples.
[0095] Table 3: Retention rate of active ingredients and color difference changes of each group of samples after accelerated aging
[0096] Results and Analysis: According to Table 3 and Figure 3 The test results showed that after accelerated aging at 54°C for 14 days, Examples 1 to 4 exhibited baicalin retention rates of 87.6%–92.1% and eugenol retention rates of 88.9%–91.2%, with color differences ranging from 1.86 to 2.38. Under these test conditions, Examples 1 to 4 showed relatively high baicalin and eugenol retention rates, and relatively small color difference changes before and after accelerated aging, indicating that the corresponding samples exhibited good retention of baicalin and eugenol and good color stability under the set accelerated aging conditions.
[0097] The above results may be related to the dispersion state of the sparingly soluble components in the impregnation system and the interactions between the various formulation components. However, this test did not directly determine the free proportion, microstructure, or specific degradation pathway of baicalin and eugenol. Therefore, it is not possible to make a definitive judgment on the specific mechanism of action of the high retention rate of baicalin and eugenol based on the existing data.
[0098] Compared to Example 1, Comparative Example 1 did not undergo cooling, and the addition of the eugenol solubilizing premix and the dropwise addition of the L-lactic acid aqueous solution were completed at 45°C. After accelerated aging, the baicalin and eugenol retention rates of Comparative Example 1 were 63.5% and 58.4%, respectively, with a color difference of 7.95. These results suggest that adding the eugenol solubilizing premix and adjusting the pH at higher temperatures may adversely affect the subsequent retention of baicalin and eugenol, as well as the stability of the appearance and color.
[0099] Comparative Example 2, with no control over the dropwise flow rate of the L-lactic acid aqueous solution, exhibited baicalin and eugenol retention rates of 74.8% and 69.1%, respectively, with a color difference of 5.32. Compared to Example 1, Comparative Example 2 showed decreased baicalin and eugenol retention rates and an increased color difference. Rapid addition of the L-lactic acid aqueous solution over a short period may cause rapid changes in the local pH of the system and may affect the dispersion state of poorly soluble components. The current results suggest that controlling the addition rate of the L-lactic acid aqueous solution may help improve the retention of baicalin and eugenol and the stability of appearance and color under accelerated aging conditions.
[0100] Comparative Examples 3, 4, and 5 did not contain trehalose, anhydrous betaine, or tea saponin, respectively. Their baicalin retention rates were 76.2%, 78.4%, and 69.1%, respectively; their eugenol retention rates were 71.4%, 73.9%, and 64.7%, respectively; and their color difference values were 4.88, 4.51, and 6.72, respectively. The baicalin and eugenol retention rates in all of these groups were lower than in Example 1, while the color difference values were higher than in Example 1, suggesting that the absence of trehalose, anhydrous betaine, or tea saponin may have a certain impact on the retention of baicalin and eugenol and the stability of the appearance and color in the impregnation solution system under accelerated aging conditions.
[0101] The absence of trehalose and anhydrous betaine may alter the aqueous environment of the system and the interactions between components; the absence of tea saponin may weaken the solubilizing and dispersing effects of the system. These predictions are consistent with the reduced retention rate of active ingredients and increased color difference observed in the corresponding comparative examples. However, the specific mechanisms of action of each component still require further analysis based on particle size, dispersion state, degradation products, and other structural characterization results.
[0102] In summary, under the accelerated aging conditions set in this test, Examples 1 to 4 generally exhibited relatively high retention rates of baicalin and eugenol, as well as relatively small color difference values. The process temperature, the rate of addition of L-lactic acid aqueous solution, and the formulation settings of trehalose, anhydrous betaine, and tea saponin may all be related to the retention of baicalin and eugenol in the impregnation solution system and the stability of its appearance and color.
[0103] Test Example 4: Experimental Description: This test is used to compare the relative response of eugenol in the headspace phase of different formulation samples after sealed heating equilibrium, as well as the retention of antibacterial activity of the samples under simulated skin drying conditions, so as to examine the relationship between changes in formulation components and the headspace distribution of eugenol and its antibacterial activity after drying.
[0104] Experimental steps: (1) Weigh 5.0 g of each of the impregnation samples prepared in Examples 1 to 4 and Comparative Examples 1 to 5, and place them in 20 mL standard headspace vials, and seal them with aluminum caps and polytetrafluoroethylene septa.
[0105] (2) Place the headspace vial in the headspace sampler of the gas chromatograph, set the equilibrium temperature to 40°C and the equilibrium time to 30 minutes, so that each sample can be gas-liquid balanced under the same conditions, and compare the headspace response differences of eugenol in the samples.
[0106] (3) Headspace gas was detected using a gas chromatograph. A non-polar capillary column, such as HP-5 or an equivalent polar column, was used. The injection port temperature was set to 220℃, the carrier gas was high-purity nitrogen, the split ratio was set to 10:1, and a flame ionization detector was used. The headspace peak area of eugenol for each sample was recorded under the same batch and instrument conditions.
[0107] The headspace chromatographic peak area of eugenol is used to compare the relative headspace air response of samples with the same initial eugenol content under the test conditions. In Examples 2 and 3, because the initial amount of eugenol added differs from that in Example 1, the headspace chromatographic peak areas are only used as test records for the corresponding samples and are not directly compared with the absolute peak areas of samples with different initial eugenol contents.
[0108] (4) Prepare artificial skin matrix sheets made of polyurethane biomimetic membrane, circular in shape, with a diameter of 6.0 mm and a thickness of 1.0 mm. Spread 20 μL of each group of sample solutions evenly on the artificial skin matrix sheets, and place them in a constant temperature incubator at 32℃ for 4 hours and 8 hours respectively to simulate the evaporation and drying process of sample moisture.
[0109] (5) Antibacterial activity was tested using the artificial skin matrix diffusion method. Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 8739, both in the logarithmic growth phase, were diluted with sterile physiological saline to prepare bacterial concentrations of approximately 1.0 × 10⁻⁶. 6 CFU / mL bacterial suspension. Take 0.1 mL of the corresponding bacterial suspension and spread it evenly on the surface of a sterile nutrient agar plate. Then, attach the above-treated artificial skin substrate to the surface of the nutrient agar plates coated with Staphylococcus aureus and Escherichia coli, respectively, ensuring that the size, attachment position and culture conditions of each substrate are consistent.
[0110] (6) Place the agar plates in a 37°C incubator for 24 hours. After incubation, measure the diameter of the inhibition zone formed around each substrate plate using calipers. The diameter of the inhibition zone includes the diameter of the substrate plate itself. Each inhibition zone is measured in two mutually perpendicular directions, and the average value is taken as the measurement result for that plate.
[0111] (7) Three independent parallel samples were set up for each group of experiments. The data in Table 4 are the average values of the three independent parallel samples.
[0112] Table 4: Results of headspace chromatographic peak area and diameter of inhibition zone after drying for each group of samples
[0113] Results and Analysis: According to Table 4 and Figure 4 The test results showed that, in samples with the same initial eugenol addition, the headspace chromatographic peak areas of eugenol in Examples 1 and 4 were 1342 and 1378, respectively; while the headspace chromatographic peak areas of eugenol in Comparative Examples 1 to 5 ranged from 2315 to 5634. Under the test conditions, the headspace gas phase response of eugenol in Examples 1 and 4 was relatively low, suggesting that the corresponding formulations may have a certain influence on the distribution of eugenol into the headspace gas phase.
[0114] The response level of eugenol in the headspace gas phase can be influenced by a variety of factors, including the initial content of eugenol in the sample, its dispersion state, the aqueous environment, and the interactions between components. Therefore, the specific state of eugenol in the system cannot be determined solely based on the headspace chromatographic peak area, nor can it be used to directly prove the existence of possible hydrogen bonding interactions, association, or mechanisms to reduce aggregation tendency in the system.
[0115] Compared to Example 1, Comparative Example 3, without the addition of trehalose, showed an increase in the headspace chromatographic peak area of eugenol from 1342 to 5634; Comparative Example 5, without the addition of tea saponin, showed a headspace chromatographic peak area of eugenol at 4426. These results suggest that, under the same initial eugenol addition, the absence of trehalose or tea saponin may be related to a certain degree of increase in the headspace response of eugenol.
[0116] The absence of trehalose may alter the aqueous environment of the system and the interaction between eugenol and other components; the absence of tea saponin may weaken the solubilizing and dispersing effects of the system. These speculations are consistent with the increased headspace chromatographic peak areas observed in Comparative Examples 3 and 5, but the relevant mechanisms still require further analysis based on the normalized initial eugenol content, particle size, partition coefficient, or other structural characterizations.
[0117] Based on the results of the inhibition zone test after drying, after being placed at 32°C for 4 hours, the diameters of the inhibition zones formed against Staphylococcus aureus and Escherichia coli in Examples 1 to 4 were 15.8–16.7 mm and 14.7–15.4 mm, respectively; after being placed for 8 hours, the corresponding inhibition zone diameters were 14.1–15.2 mm and 13.0–13.9 mm, respectively. These results show that the diameter of the inhibition zones in each example decreased to some extent with prolonged placement time, but relatively clear inhibition zones were still formed after 8 hours of treatment.
[0118] Compared to Example 1, the inhibition zone diameters of Comparative Examples 1 to 5 were generally smaller after the same storage time. Specifically, after 8 hours of treatment, Comparative Example 3 showed inhibition zone diameters of 7.4 mm and 6.5 mm against Staphylococcus aureus and Escherichia coli, respectively; the corresponding inhibition zone diameters of Comparative Example 5 were 9.1 mm and 8.3 mm, respectively. These results suggest that the absence of trehalose or tea saponins may have a certain impact on the retention of antibacterial activity after the samples are dried.
[0119] It should be noted that the diameter of the inhibition zone is not only related to the amount of active ingredient remaining on the substrate surface, but may also be affected by factors such as the diffusion capacity of the active ingredient in the agar medium, the water content of the substrate, and the combined effects of various active ingredients. Therefore, existing inhibition zone results are mainly used to compare the antibacterial activity of different samples after drying, and should not be directly converted into the actual residual amount of active ingredient on the substrate surface.
[0120] In summary, under the test conditions, the sample samples generally exhibited a relatively low head-phase response to eugenol and relatively good retention of antibacterial activity after drying. The formulation of trehalose and tea saponins may be related to these test results, but their specific mechanisms of action still need to be verified through further experiments.
[0121] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A production process for plant-based composite antibacterial nursing wipes, characterized in that, Includes the following steps: S1. Add deionized water to the main reactor equipped with a jacketed temperature control system and a mechanical stirrer, turn on the heating, and maintain the water temperature at the first set temperature. S2, add anhydrous betaine and trehalose in sequence and stir until dissolved; add L-arginine to make the system alkaline pH value, then add baicalin and continue stirring to form a homogeneous solution; S3, turn off heating, start cooling circulation, cool the liquid to a second set temperature of 10 to 15°C at a set cooling rate, and maintain this temperature; S4, while maintaining the second set temperature and continuous stirring, the eugenol solubilized premixed solution formed by premixing dipropylene glycol, eugenol and tea saponin is pumped into the main reactor at a uniform rate and mixed evenly. S5, under the condition of maintaining the second set temperature and continuous stirring, add L-lactic acid aqueous solution dropwise into the main reaction vessel, adjust the dropwise flow rate of L-lactic acid aqueous solution to keep the pH value decreasing rate within the specified range of 0.05 to 0.15 pH value units per minute, and stop the dropwise addition when the pH of the system reaches 5.0 to 5.
5. This stop dropwise addition point is the low temperature acidification endpoint; S6, stop cooling and allow the temperature of the liquid to rise to 20 to 25°C, stir to balance; add deionized water and fine-tune the pH to bring the final pH of the system to 5.0 to 5.5, and stir evenly; S7, the liquid is conveyed through the microporous filter membrane, the filtrate is collected, and the plant composite antibacterial impregnation liquid is obtained; S8. The obtained impregnation liquid is applied to the spunlace nonwoven fabric substrate, folded and cut, and then sealed in packaging material to obtain plant composite antibacterial care wipes.
2. The production process of the plant-based composite antibacterial nursing wipes according to claim 1, characterized in that, The raw materials used in the production process comprise the following components in parts by weight: The initial amount of deionized water added is 880.0 to 920.0 parts by weight, determined based on the amounts of other components and pH adjustment solution, so that the final amount of deionized water can be replenished to 1000.0 parts by weight. Anhydrous betaine: 2.0 to 8.0 parts; Trehalose: 5.0 to 15.0 parts; L-Arginine: 0.5 to 3.0 parts; Baicalin: 1.0 to 5.0 parts; L-lactic acid aqueous solution: the amount required to bring the system to the specified pH; Added deionized water: the amount required to bring the total weight of the system to 1000.0 parts by weight; In the eugenol solubilized premix, the weight parts of dipropylene glycol, eugenol and tea saponin are respectively: 10.0 to 30.0 parts of dipropylene glycol, 0.1 to 1.0 parts of eugenol and 1.0 to 5.0 parts of tea saponin.
3. The production process of the plant-based composite antibacterial nursing wipes according to claim 2, characterized in that, The preparation method of the eugenol solubilized premix is as follows: In the auxiliary reaction vessel, the temperature of the materials inside the auxiliary reaction vessel is controlled at 20 to 25°C. The dipropylene glycol, eugenol and tea saponin are added in sequence. The stirrer is turned on and the speed is set to 200 to 400 rpm. The mixture is mixed for 15 to 30 minutes to obtain a uniform and transparent eugenol solubilized premix.
4. The production process of the plant-based composite antibacterial nursing wipes according to claim 1, characterized in that, In step S1, the first set temperature is 40 to 45°C; in step S2, after adding L-arginine, the stirring speed is maintained at 100 to 150 rpm, and after adding baicalin, the stirring is continued for 15 to 30 minutes.
5. The production process of the plant-based composite antibacterial nursing wipes according to claim 1, characterized in that, In step S3, the cooling rate is 1 to 3 °C / min.
6. The production process of the plant-based composite antibacterial nursing wipes according to claim 1, characterized in that, In step S4, the eugenol solubilized premix is pumped into the main reactor at a constant rate over 5 to 15 minutes.
7. The production process of the plant-based composite antibacterial nursing wipes according to claim 1, characterized in that, In step S5, the L-lactic acid aqueous solution is an L-lactic acid aqueous solution with a mass fraction of 10.0% based on L-lactic acid.
8. The production process of the plant-based composite antibacterial nursing wipes according to claim 1, characterized in that, In step S6, the temperature of the recovered liquid is 20 to 25°C, and the stirring equilibrium time is 20 to 40 minutes. During fine-tuning, an L-lactic acid aqueous solution with a mass fraction of 10.0% based on L-lactic acid or an L-arginine aqueous solution with a mass fraction of 10.0% based on L-arginine is used for adjustment. Finally, deionized water is added to make the total weight of the system reach 1000.0 parts by weight.
9. The production process of the plant-based composite antibacterial nursing wipes according to claim 1, characterized in that, In step S7, the pore size of the microporous filter membrane is 0.5 to 2.0 μm; after the feed liquid is transported through the microporous filter membrane, the filtrate is collected, which is the plant composite antibacterial impregnation solution.
10. The production process of the plant-based composite antibacterial nursing wipes according to claim 1, characterized in that, In step S8, the impregnation liquid is applied to the spunlace nonwoven fabric substrate at a mass ratio of 1:2.5-4.5 between the unimpregnated spunlace nonwoven fabric substrate and the impregnation liquid. The substrate is then folded, cut, and sealed in packaging material to obtain the finished product.